Application of raw and biochared Moringa oleifera seed powder for the removal of nitrobenzene from aqueous solutions. Issue 53 (13th November 2016) - Tavengwa, Nikita Tawanda; Cukrowska, Ewa; Chimuka, Luke
Abstract: Low cost and locally available Moringa seed powder as a potential biosorbent was tested for its effectiveness in the removal of nitrobenzene (NB) from aqueous solution. Biochared Moringa oleifera seed powder was also used to compare its performance in the uptake of NB from aqueous solution. Fourier transform infrared spectroscopy fingerprint region of the biochared M. oleifera seed powder was clearer as compared to the raw. Pores observed by the scanning electron microscopy analysis were found to be 0.84 and 1.23 cm 3 g −1 (by BET analysis) for the raw and biochared M. oleifera seed powder, respectively. The carbon elemental analysis by energy-dispersive X-ray spectroscopy was 80 and 70% for the raw and biochared M. oleifera seed powder, respectively. The removal efficiencies of the two sorbents were evaluated using factors such as solution pH, biosorbent dosage, contact time and initial NB concentration. A basic pH of 11 was found to be optimum for the uptake of NB for both sorbents. The sorption equilibration time of NB at 25°C was about 50 min, and the optimal NB removal efficiency was achieved with a dosage of 12.5 g L −1 . The pseudo-second-order was found to fit the kinetic data better with the calculated sorption capacity of NB of 0.084 and 0.071 mg g −1 onto the raw and biochared M. oleifera seed powder sorbent. The limit of detection and limit of quantification values for NB determination by HPLC-UV were found to be 11.54 and 38.46 μg L −1, respectively.